Plasma pharmacokinetics, pulmonary disposition, and safety of subcutaneous gamithromycin in alpacas. Issue 3 (16th February 2022) - Gordon, Emma; Cebra, Christopher K.; Stang, Bernadette V.; Christensen, John Mark; Alshahrani, Sultan. M.; Duong, Thanh; Huang, Rose; Nosky, Bruce
Abstract: The study objective was to determine the disposition of gamithromycin in plasma, peripheral blood polymorphonuclear cells (PMNs), pulmonary epithelial lining fluid (PELF), and bronchoalveolar lavage (BAL) cells in alpacas. A single subcutaneous injection of gamithromycin (6.6 mg/kg) was administered to six healthy adult alpacas. At various time points after administration, gamithromycin concentrations were analyzed via LC‐MS/MS in plasma, PMNs, PELF, and BAL cells until Day 14 post‐injection. Plasma gamithromycin concentrations were measured in all six alpacas; the remaining three body compartments were analyzed in four alpacas. Gamithromycin rapidly concentrated in blood PMNs, BAL cells, and PELF. Shorter T max, and lower C max, and AUC were observed in plasma than in the other three compartments. C max was highest in BAL cells (26001.80 ± 12400.00 ng/ml) and PMNs (2573.00 ± 963.30 ng/ml) compared to PELF (660.80 ± 413.70 ng/ml) and plasma (452.30 ± 196.20 ng/ml). Mean terminal half‐lives were 72.60 ± 14.10 h in plasma, 56.60 ± 10.60 h in PELF, 62.80 ± 85.30 h in PMNs, and 93.60 ± 124.80 h in BAL cells. No injection site reactions occurred. One alpaca developed colic but no other adverse reactions were noted. Overall, gamithromycin was highly concentrated in white blood cells and pulmonary fluids/cells. Clinical utilization of gamithromycin in alpacas should be done with caution until further investigation of potential for colic.